2013
DOI: 10.1007/s00259-013-2359-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of the 18-kDa translocator protein (TSPO) with [18F]FEDAA1106 and PET does not show increased binding in Alzheimer’s disease patients

Abstract: This study suggests that TSPO imaging with [(18)F]FEDAA1106 does not enable the detection of microglial activation in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 33 publications
1
45
1
Order By: Relevance
“…Seven ligands were used; 19 studies used PK11195,18–36 two studies used DAA1106,37–38 one study used vincopetine,39 two studies used DED,40–41 two studies used PBR28,42–43 one study used FEDAA110644 and one study used AA 45. Five of these seven ligands (PK11195, DAA1106, vincopetine, PBR28, FEDAA1106) bind the TSPO on activated microglia, one (DED) binds to MAO-B in activated astrocytes and one (AA) images a metabolic by-product of microglial-induced neuroinflammation 45.…”
Section: Resultsmentioning
confidence: 99%
“…Seven ligands were used; 19 studies used PK11195,18–36 two studies used DAA1106,37–38 one study used vincopetine,39 two studies used DED,40–41 two studies used PBR28,42–43 one study used FEDAA110644 and one study used AA 45. Five of these seven ligands (PK11195, DAA1106, vincopetine, PBR28, FEDAA1106) bind the TSPO on activated microglia, one (DED) binds to MAO-B in activated astrocytes and one (AA) images a metabolic by-product of microglial-induced neuroinflammation 45.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in TSPO expression has been observed during the onset of disease in amytrophic lateral sclerosis (ALS) patients (147). Similarly, brains of subjects with mild cognitive impairment (MCI), who are at an increased risk of developing Alzheimer's disease (AD), or subjects with mild and early forms of AD, exhibit higher ligand binding compared to age-matched controls (148,149) although other studies contradict this observation (150). Widespread glial activation is likewise associated with the pathological process that occurs in Parkinson's disease (PD) and TSPO ligands have shown increased binding profiles in rat models mimicking the early stages the disease (151).…”
Section: Inflammatory Brain Conditionsmentioning
confidence: 87%
“…In the aim to explore this process in vivo, a number of PET tracers of TSPO were developed in recent years as an alternative to the reference ligand [ 11 C]PK-11195 ). In AD, clinical studies have found no detection (Varrone et al 2013) or increase of TSPO density (Kreisl et al 2013, Schuitemakeret al 2013 (Martin et al 2010;Boutin et al 2013), traumatic brain injury (Wang et al 2014) and epilepsy (Harhausen et al 2013), and has begun to be used in clinical studies (Corcia et al 2012) although no data are to date available in AD. …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%